Environmental pollutants and diseases of sexual development in humans and wildlife in South Africa: harbingers of impact on overall health? - Bornman, M.S. (Riana); Bouwman, Hindrik (Wiley, 2012)
This study deals with disorders of sexual development in humans, wildlife and animals in an urban nature reserve (RNR) and a currently DDT-sprayed malarial area. High levels of oestrogenic chemical residues in water, sediment and tissue; skewed sex ratios; reduced biodiversity; gonadal malformations in sharptooth catfish and freshwater snails; intersex in catfish; and impaired spermatogenesis in catfish and striped mouse are of serious concern in the RNR. Persistent eggshell thinning in African darter eggs, intersex in male Mozambican tilapia, follicular atresia in females and impaired spermatogenesis in males following laboratory exposure of parent fish to environmentally relevant DDT and DDE concentrations, and abnormalities in freshwater snails were found in the DDT-sprayed area. Human studies related to DDT exposure indicated impaired semen quality, a weak association with sperm chromatin defects and higher risks for external urogenital birth defects in those who were born to mothers whose houses were sprayed and those who were homemakers (stay at home mother) instead of being employed. These findings indicate that diseases of sexual development occurred in both human and wildlife populations exposed to environmental endocrine disruptor chemicals in South Africa. The chemical mixtures, possibly related to disorders of sexual differentiation (DSD), were very different between the two. However, DSD occurred concurrently in the malarial area, possibly indicating that humans and wildlife shared exposures. Moreover, it emphasizes the importance of suspecting disease in the other when disease is found in either human or wildlife populations